Health care providers' awareness of breastfeeding practice recommendations during COVID-19 pandemic and associated factors in Northwest Ethiopia, 2021: A multicenter study. - Azmeraw Ambachew Kebede; Birhan Tsegaw Taye; Kindu Yinges Wondie; Agumas Eskezia Tiguh; Getachew Azeze Eriku; Muhabaw Shumye Mihret (PLoS ONE)
Background Prevention of coronavirus disease 2019 (COVID-19) transmission to newborns is one of the basic components of perinatal care in the era of the COVID-19 pandemic. As such, scientific evidence is compulsory for evidence-based practices. However, there was a scarcity of evidence on health care providers' awareness of breastfeeding practice recommendations during the COVID-19 pandemic in Ethiopia, particularly in the study setting. Objective The study aimed at assessing healthcare providers' awareness of breastfeeding practice recommendations during the COVID-19 pandemic and associated factors among healthcare providers in northwest Ethiopia, 2021. Methods A multicenter cross-sectional study was conducted among 405 healthcare providers working in hospitals of Gondar province from November 15, 2020, to March 10, 2021. A simple random sampling technique was employed to select the study subjects. Data were collected via a structured-self-administered questionnaire. EPI INFO version 7.1.2 and SPSS version 25 were used for data entry and analysis respectively. Binary logistic regression analyses were done to identify associated factors and the adjusted odds ratio (AOR) with its 95% confidence interval (CI) at a p-value of <0.05 was used to declare significant association. Results The healthcare providers' awareness of breastfeeding practice recommendations during the COVID-19 pandemic was 40.7% (95% CI: 35.9, 45.6). Working in a tertiary hospital (AOR = 3.69; 95% CI: 2.24, 6.08), using COVID-19 guideline updates (AOR = 3.34; 95% CI: 2.1, 5.3), being trained on COVID-19 (AOR = 2.78; 95% CI: 1.74, 4.47), owning a smartphone and/or a computer (AOR = 2.26; 95% CI: 1.39, 3.68), and perceiving that COVID-19 is dangerous (AOR = 1.78; 95% CI: 1.05, 3.01) were factors positively associated with healthcare providers' awareness of breastfeeding practice recommendations during the pandemic of COVID-19. Conclusion Only two in five healthcare providers were aware of recommendations on breastfeeding practice during the COVID-19 pandemic and related to information of accessibility information on COVID-19. Therefore, expanding COVID-19 related information through the provision of COVID-19 training and guidelines to all levels of hospitals would improve health care providers' awareness of breastfeeding practice recommendations amid the COVID-19 pandemic.